Human parvovirus B19 vertical infection and hydrops fetalis: A case report - Boggio, Gabriel Amilcar (2024)
Non-immune hydrops fetalis represents a diagnostic challenge in high-risk pregnant women. Vertical infection with human parvovirus B19 (B19V) is a possible cause. National guidelines propose maternal serologic screening (IgG/IgM), which may be insufficient in some situations. We report a case of vertical B19V infection with difficulties in prenatal diagnosis. Preterm newborn, normal weight (2950 g), born to a 30-year-old mother with anemia and hydrops fetalis (week 17). Cardiac, chromosomal, isoimmunization-Rh, and usual infectious causes (TORCH) were ruled out. Maternal serology for B19V showed IgG+ and IgM-, and the diagnosis was dismissed. The newborn presented abdominal distension (ascites), anemia, and jaundice. Postnatal results confirmed the diagnosis with DNA+ for B19V. Discharge at 17 days with good evolution. The protocol for B19V screening in vertical infection needs to be revised by incorporating early molecular studies (PCR) from the early stages of gestation to optimize the diagnosis and treatment of patients with this congenital infection.